Studi Fenomenologi terhadap Pasien Hipertensi - Ruth Jelina Br Sitepu; Lyna M. N. Hutapea (Jurnal Keperawatan Silampari, 2022)
This study aims to examine phenomenological studies of hypertensive patients. This research method is qualitative research with a descriptive phenomenological approach that uses the Colaizzi model. Research results: Identified in 4 themes, namely: 1. Knowledge, 2. Activities, 3. Stress/Emotional Levels, 4. Family History. In conclusion, Through the experience of clients who suffer from hypertension, information about knowledge, activities, stress/emotional levels, and family history are essential in influencing their health condition both before experiencing hypertension and after suffering from hypertension. Keywords: Hypertension, Experience, Qualitative